New quinoline-based triazole hybrid analogs as effective inhibitors of α-amylase and α-glucosidase: Preparation, in vitro evaluation, and molecular docking along with in silico studies - Khan, Yousaf; Iqbal, Shahid; Shah, Mazloom; Maalik, Aneela; Hussain, Rafaqat; Khan, Shoaib; Khan, Imran; Pashameah, Rami Adel; Alzahrani, Eman; Farouk, Abd-ElAziem; Alahmdi, Mohammed Issa; Abd-Rabboh, Hisham S. M. (Frontiers in Chemistry, 2022)
The 7-quinolinyl-bearing triazole analogs were synthesized (1d–19d) and further assessed in vitro for their inhibitory profile against α-amylase andα-glucosidase. The entire analogs showed a diverse range of activities having IC50 values between 0.80 ± 0.05 µM to 40.20 ± 0.70 µM (α-amylase) and 1.20 ± 0.10 µM to 43.30 ± 0.80 µM (α-glucosidase) under the positive control of acarbose (IC50 = 10.30 ± 0.20 µM) (IC50 = 9.80 ± 0.20 µM) as the standard drug. Among the synthesized scaffolds, seven scaffolds 12d, 10d, 8d, 9d, 11d, 5d, and 14d showed excellent α-amylase and α-glucosidase inhibitory potentials with IC50 values of 4.30 ± 0.10, 2.10 ± 0.10, 1.80 ± 0.10, 1.50 ± 0.10, 0.80 ± 0.05, 5.30 ± 0.20, and 6.40 ± 0.30 µM (against α-amylase) and 3.30 ± 0.10, 2.40 ± 0.10, 1.20 ± 0.10, 1.90 ± 0.10, 8.80 ± 0.20, 7.30 ± 0.40, and 5.50 ± 0.10 µM (against α-glucosidase), respectively, while the remaining 12 scaffolds 19d, 8d, 17d, 16d, 15d, 7d, 4d, 3d, 1d, 2d, 13d and 6 d showed less α-amylase and α-glucosidase inhibitory potentials than standard acarbose but still found to be active. Structure–activity connection studies also showed that scaffolds with electron-withdrawing groups like -Cl, -NO2, and -F linked to the phenyl ring had higher inhibitory potentials for -amylase and -glucosidase than scaffolds with -OCH3, -Br, and -CH3 moieties. In order to better understand their binding sites, the powerful scaffolds 11d and 9d were also subjected to molecular docking studies. The results showed that these powerful analogs provide a number of important interactions with the active sites of both of these targeted enzymes, including conventional hydrogen bonding, pi–pi stacking, pi–sulfur, pi–anion, pi–pi, pi–sigma, T-shaped, and halogen (fluorine). Furthermore, various techniques (spectroscopic), including 1H, 13C-NMR, and HREI-MS mass, were used to explore the correct structure of newly afforded hybrid scaffolds based on quinoline-bearing triazole ring.